Uso de backtracking para generación de sucesiones sonares (2013)
In a frequency hopping radar system, the signal consists of one or more frequencies chosen from a set of m available frequencies for transmission at each of a set of n consecutive time intervals. Such a signal can be represented by an m X n matrix of 0’s and 1’s in which each column contains exactly one 1. When the signal is reflected back to the observer, it is shifted in both time and frequency. The amounts of these shifts can be used to determine both distance and velocity. The amounts of shifts, in turn, are determined by comparing all shifts of a replica of the transmitted signal with the signal received. This is equivalent to counting the number of coincidences of 1s in a shifted version of the matrix of 0’s and 1’s that represents the signal. The number of such hits as a function of shifts in time and frequency is called the auto-correlation function. A sonar array is a m x n pattern which has at most one hit in its auto-correlation function. In a multiple target environment, one pattern is sent for each target. In this work we study algorithms that generate sonar type sequences for one and multiple target recognition. The use of backtracking technique to find sonar sequences is presented as a particular case.